Community-Acquired Pneumonia in Canada During Coronavirus Disease 2019. (4th February 2022) - Mandell, Lionel A; Zhanel, George G; Rotstein, Coleman; Muscedere, John; Loeb, Mark; Johnstone, Jennie
Abstract: Dealing with coronavirus disease 2019 (COVID-19) has been a monumental test of medical skills and resources worldwide. The management of community-acquired pneumonia (CAP) can at times be difficult, but treating CAP in the setting of COVID-19 can be particularly trying and confusing and raises a number of challenging questions relating to etiology, diagnosis, and treatment. This article is based on the authors' experiences and presents an overview of how CAP during COVID-19 is handled in Canada. We touch on the issues of microbial etiology in patients with CAP in the setting of COVID-19 as well as diagnostic, site of care, and treatment approaches. Published guidelines are the basis of management of CAP and are discussed in the context of Canadian data. We also outline the usual treatment approaches to COVID-19, particularly in patients who have been hospitalized. Abstract : This article represents the viewpoints of the authors on the management of community-acquired pneumonia in Canada during the COVID-19 pandemic. The issues, difficulties, and challenges pertaining to the etiology, diagnosis, and treatment of these patients are discussed.